Koordinasi Pembangkit Hidro-Termal di Sistem Sulawesi Selatan dan Sulawesi Barat - Ryan M. Mangewa; Lily S. Patras; Maickel Tuegeh; Fielman Lisi (Jurnal Teknik Elektro dan Komputer, 2013)
Abstrack--Electric power system in South Sulawesi and West Sulawesi supplied by hydro power plants and thermal power plants . Coordination of hydro and thermal power plants aimed to determine the pattern of optimal operation of generating units with minimal operating costs . Coordination of hydro and thermal power generation is done by adjusting the operating schedule of each generate unit . Generating units with low operating costs of the operation to carry the base load of the system , particularly the hydro generating units . Further thermal generating units with higher operating costs are operated to meet the remaining load . Operation of hydro generating units are set to determine the pattern of operation based on the pattern of the load with gave attention to constraint generation and water consumption . Dynamic Programming method is used to determine the power of thermal generating covered by each units and to determine the possible optimal combination of operating thermal generating units. Scheduling and loading were done after power obtained from each hydro and thermal generating units . By clicking coordinate hydro - thermal power system in South Sulawesi and West Sulawesi using Dynamic Programming the total operating expenses of Rp 2,672,519,124.22 . While total operating cost incurred by PT . PLN ( Persero ) is Rp 2,980,499,154.18 . Keywords :optimal operation , generating hydro - thermal coordination